Pengaruh bimbingan karir dan praktek kerja lapangan terhadap perencanaan karir siswa kelas XII Administrasi Perkantoran SMK Karya Pembangunan Kabupaten Tangerang - Alwan Dzaki, Rafi; Jaka Slameta; Rika Nurhidayah (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
Process Career maturity begins with the development of curiosity and digging to obtain information. Career development can be carried out well, this is due to the career guidance provided by several people so that they are ready to work. The career guidance in question is a mentoring activity or a process of providing assistance to individuals on an ongoing and systematic basis, which is carried out by a person so that the individual can understand the skills that the individual has. Based on the results of the analysis carried out by the researcher, the conclusions that can be drawn from this research are Career Guidance influences the Career Planning of Class XII Students in Office Administration at Karya Pembangunan Vocational School. This is because the calculated t value of the Career Guidance variable is 9.181 which is greater than the t table value which is 1.99125. Fieldwork Practices influence the Career Planning of Class XII Office Administration Students at Karya Pembangunan Vocational School. This is because the Field Work Practice variable has a calculated t value of 9.489 which is greater than the t table value of 1.99125. Career Guidance and Field Work Practices influence the Career Planning of Class XII Students in Office Administration at Karya Pembangunan Vocational School. This is because the Career Guidance and Field Work Practices variables have a calculated F of 892.733 which is greater than the f table value of 3.12 with a significance level of 0.000 or <0.05.